COVID-19 Pandemic and Beyond: Considerations and Costs of Telehealth Exercise Programs for Older Adults With Functional Impairments Living at Home—Lessons Learned From a Pilot Case Study. Issue 8 (5th May 2020) - Middleton, Addie; Simpson, Kit N; Bettger, Janet Prvu; Bowden, Mark G
Abstract: Objective: The purpose of this study was to describe the process and cost of delivering a physical therapist–guided synchronous telehealth exercise program appropriate for older adults with functional limitations. Such programs may help alleviate some of the detrimental impacts of social distancing and quarantine on older adults at-risk of decline. Methods: Data were derived from the feasibility arm of a parent study, which piloted the telehealth program for 36 sessions with 1 participant. The steps involved in each phase (ie, development, delivery) were documented, along with participant and program provider considerations for each step. Time-driven activity-based costing was used to track all costs over the course of the study. Costs were categorized as program development or delivery and estimated per session and per participant. Results: A list of the steps and the participant and provider considerations involved in developing and delivering a synchronous telehealth exercise program for older adults with functional impairments was developed. Resources used, fixed and variable costs, per-session cost estimates, and total cost per person were reported. Two potential measures of the "value proposition" of this type of intervention were also reported. Per-session cost of $158 appeared to be a feasible business case, especially if the physical therapist to trained assistant personnel mix could be improved. Conclusions: The findings provide insight into the process and costs of developing and delivering telehealth exercise programs for older adults with functional impairments. The information presented may provide a "blue print" for developing and implementing new telehealth programs or for transitioning in-person services to telehealth delivery during periods of social distancing and quarantine. Impact: As movement experts, physical therapists are uniquely positioned to play an important role in the current COVID-19 pandemic and to help individuals who are at risk of functional decline during periods of social distancing and quarantine. Lessons learned from this study's experience can provide guidance on the process and cost of developing and delivering a telehealth exercise program for older adults with functional impairments. The findings also can inform new telehealth programs, as well as assist in transitioning in-person care to a telehealth format in response to the COVID-19 pandemic.